A Study on Ultrasonic Elliptical Vibration Cutting of Inconel 718 - Zhao Haidong; Zou Ping; Ma Wenbin; Zhou Zhongming (Shock and Vibration)
Inconel 718 is a kind of nickel-based alloys that are widely used in the aerospace and nuclear industry owing to their high temperature mechanical properties. Cutting of Inconel 718 in conventional cutting (CC) is a big challenge in modern industry. Few researches have been studied on cutting of Inconel 718 using single point diamond tool applying the UEVC method. This paper shows an experimental study on UEVC of Inconel 718 by using polycrystalline diamond (PCD) coated tools. Firstly, cutting tests have been carried out to study the effect of machining parameters in the UEVC in terms of surface finish and flank wear during machining of Inconel 718. The tests have clearly shown that the PCD coated tools in cutting of Inconel 718 by the UEVC have better performance at 0.1 mm depth of cut as compared to the lower 0.05 mm depth of cut and the higher 0.12 or 0.15 mm depth of cut. Secondly, like CC method, the cutting performance in UEVC increases with the decrease of the feed rate and cutting speed. The CC tests have also been carried out to compare performance of CC with UEVC method.